CO Activation by (Diphosphane)platinum(0): Carbonate and Acetone Formation – Experimental and Mechanistic Study. Issue 22 (31st May 2013) - Nicolas, Emmanuel; Nocton, Grégory; Mézailles, Nicolas
Abstract: The platinum(II) complex [(dcpp)Pt(C7 H7 )H] (1 ) [dcpp = 1, 3‐bis(dicyclohexylphosphanyl)propane] reacts under 1 atm of CO to form the bis(carbonyl) complex of Pt 0, [(dcpp)Pt(CO)2 ] (2 ). Complex2 slowly crystallizes in toluene solution to form crystals of the Pt 0 dimer [(dcpp)(η 1 ‐CO)Pt{μ‐C(O)}Pt(dcpp)] (3 ) in which one Pt atom is only three‐coordinated with the diphosphane dcpp and one μ‐C(O), while the other is coordinated in a tetrahedral arrangement with one μ‐C(O) and one η 1 ‐CO. Complexes2 and3 were characterized in solution by 31 P NMR spectroscopy, and complex3 readily reacts with O2 to form the carbonate complex, [(dcpp)Pt(CO3 )] (4 ). The reaction of the dimeric complex3 with MeI allows the insertion of a methyl group into the carbonyl group to form the Pt II complex [(dcpp)Pt(C(O)Me)I] (5 ). Reaction of another equivalent of MeI with complex5 leads to the formation and elimination of acetone and the bis(iodide) complex [(dcpp)PtI2 ] (6 ). X‐ray crystal structures of complexes3 and4 are reported along with DFT calculations and mechanistic studies of the formation of3, 4, 5, and6 . Abstract : The easy access at room temperature to a monocarbonyl–Pt 0 complex source allows the addition of stoichiometric amounts of MeI and the formation of acetone, while a Pt II carbonate complex forms in the presence of O2 . Structural insights into the reaction products and calculated mechanisms are reported.